Analysis of Students Difficulties in Solving Mathematics Problems on Number Operations Material Using Qualitative Descriptive Methods for Class IV Students - Alya Novita; Mailani, Elvi (Indonesian Journal of Advanced Research, 2023)
This research aims to determine students' difficulties in solving mathematics questions on number operations by analyzing using qualitative descriptive methods for Class IV students at SDN 101765 Bandar Setia. The analytical method that will be used in this research is a qualitative descriptive method based on Newman's theory. The results of the research show that there are learning difficulties experienced by students at this school, based on findings in the field the learning difficulties experienced are difficulty reading and understanding questions, processing and transformative difficulties, difficulty writing answers. Difficulty reading and understanding the questions was seen in students who were unable to answer the researcher's questions about fraction operations. The results of the document show that there are still some students who have not been able to complete fraction calculations. Processing and transformative difficulties were seen in students who were unable to answer the researcher's questions about fraction operations. The document results show that there are still some students who have not been able to complete fraction calculations. And difficulties in writing answers are seen in students who have been able to do all the steps, but when it comes to determining the answer they cannot. In this research, students were still unable to multiply the answers with the correct answer.